Estate Planning - Josephine Turner; Vervil Mitchell (EDIS, 2002)
This document is FCS 7027, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2002. First published: July 1978. Revised: September 2002.